Comparative Study of Carotenoids Content in Ripe and Unripe Oil Palm Fresh Fruit Bunches - Puteh, Abdul Quddus; Mohd Shahrome, Anith Arina; Haji Razali, Mohd Hudzari; Sulaiman, Alawi (International Journal of Integrated Engineering, 2022)
Currently Elaies Guineensis or oil palm is the most widely planted commodity crop in Malaysia and has a very large impact to the country’s economy. At the same time, the industry also produces huge amount of oil palm waste materials such as Unripe Fresh Fruit Bunche (FFB). Each year million tons of Unripe FFB could not be processed in the mill and were disposed-off and thus posed additional threats to the environment. The objective of this study was to recycle the Unripe FFB and compared the carotenoids content with the Ripe FFB. Carotenoids is the natural chemical compounds which gives palm oil its orange red color. The compound is good for human health as it can strengthen body immunity system and act as antioxidant The experiment was conducted by collecting fruits from three (3) samples of Ripe FFB and Unripe FFB. The selected fruits were then sterilized, and Crude Palm Oil (CPO) was extracted. The analysis of oil samples was conducted using Near Infrared Spectroscopy Diode Array (NIRS DA) 1650. Result for the carotenoids showed that mean for the Ripe FFB was 968.07 ppm and for the Unripe FFB was 927.37 ppm. The Free Fatty Acids (FFA) were 22.08 and 14.47 respectively which indicated that the fruits were badly bruised during the processing. This study showed that the carotenoids content in Unripe FFB is comparable with the Ripe FFB and thus it can be concluded that Crude Palm Oil (CPO) from Unripe FFB can be used for carotenoids extraction instead of rejected or disposed-off to the environment.